Mobile Multicast Source Support in PMIPv6 Networks - Lili Wang and Shuai Gao and Hongke Zhang and Thomas C. Schmidt and Jianfeng Guan (EURASIP journal on wireless communications and networking : EURASIP JWCN, 2013)
With the widespread use of multimedia contents via mobile nodes (MNs), IP mobile multicast becomes more important for wireless, mobile, and ubiquitous multimedia applications. Until now, many research efforts have been made to provide IP multicast for the MNs. However, the existing mobile multicast schemes mostly focus on the mobility of receivers based on the host-based mobility solution that requires the MN to participate in the mobility management. Recent work has shown that service connectivity for mobile multicast sources is still a problem and attracts very little concern. With the development of the network-based mobility support protocol, mobile multicast source support schemes in Proxy Mobile IPv6 (PMIPv6) networks are needed urgently. In this paper, we propose a base solution (BS) and also a direct multicast routing scheme (DMRS) for mobile multicast source support in PMIPv6 networks. In the BS, the multicast listener discover (MLD) proxy function is adopted to transmit multicast data through the PMIPv6 tunnel. The DMRS can provide locally optimized traffic flows and avoid inefficient routing present in the BS. We evaluate and compare the performance of the proposed schemes with the Mobile IP bidirectional tunneling (MIP-BT) and Mobile IP remote subscription (MIP-RS) schemes by theoretical analysis and also implement the proposed schemes on the test-bed. The numerical results show that the BS and DMRS outperform the MIP-BT and MIP-RS in terms of signaling cost. Meanwhile, the experimental results verify the feasibility and validity of our proposed schemes. Furthermore, we study the optimal PMIPv6 domain size to reduce the total signaling cost for the proposed schemes.
Keywords: Mobile Node; Multicast Tree; Multicast Group; Local Mobility Anchor; Internet Engineer Task Force